In Silico Approach: Effect of the Oxidation Iron State (Heme-Group) in Steroidogenesis Pathways - David Mora-Martinez; Jorge Organista-Nava; Jesús Sandoval-Ramirez; Berenice Illades-Aguiar; Alan Carrasco-Carballo (Journal of Molecular Docking, 2022)
One of the main design features of enzyme regulators for the CYPs is the presence of a heme-group and different oxidation states in iron atoms. The selective inhibition of a CYP-enzyme can help to reduce the formation of steroidal molecules that causes undesirable disorders and is, therefore a topic of great biochemical-pharmaceutical interest. The present work carried out an analysis of effect on the coupling-energy of the iron core according to its changes from oxidation Fe(II) to Fe(III) state, over inhibitors and substrates, in a particular enzyme. Two crystals from CYP21A2, CYP11A1, CYP17A1 and CYP19A1 enzymes were selected, assigning the oxidation states separately in each case. It was highlighted that for CYP11A1 and CYP19A1 enzymes, no significant difference was observed in coupling energies between Fe oxidation state and crystal stereo-disposition. This last can be used to analyze their congruence towards the reported biological data. For CYP17A1, the ideal crystal for inhibitors design is 6CHI since the crystal with 4NKV presented differences in all the molecules analyzed since the oxidation state of the iron atom changes the molecule's orientation in the enzyme coupling. In contrast, in CYP21A2, no changes were observed. A greater biological congruence with 5BVU was observed because the coupling energies concur with the selectivity of the enzyme towards its endogenous substrates and reported inhibitors. It was concluded that the effect of the oxidation state of iron on the Binding Coupling Energy (BCE) depends directly on the functional groups attached to the steroidal molecule and their stereo-disposition.